Analysis of Price Perception and Celebrity Endorser on Purchasing Decisions for Skintific Skincare Products of UNRI Gen Z Graduate Students with Intervening Variables Online Customer Review - Jayanti, Fitri; Zulkarnain , Zulkarnain; Machasin, Machasin (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study was conducted to determine Analysis of Price Perception and Celebrity Endorser on Purchasing Decisions for Skintific Skincare Products of UNRI Gen Z Graduate Students with Intervening Variables Online Customer Review. The study was conducted by distributing questionnaires to 210 active postgraduate students at the University of Riau born between 1996 and 2010. The results of this study indicate that Celebrity Endorser, Online Customer Review, and price perception have a positive effect on purchasing decisions. Celebrity Endorser and price perception have a positive effect on Online Customer Review. Online Customer Review significantly mediates the relationship between Celebrity Endorser and purchasing decisions. Online Customer Review significantly mediates the relationship between price perception and purchasing decisions.